The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1371/journal.pone.0198260
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of the novel bacterial blight resistance gene Xa38 into the genetic background of elite rice variety Improved Samba Mahsuri

Abstract: Bacterial blight (BB) in rice caused by Xanthomonas oryzae pv. oryzae (Xoo) is a major global production constraint, particularly in irrigated and rain-fed lowland areas. Improved Samba Mahsuri (ISM) is an elite, high-yielding, fine-grain type, BB-resistant rice variety possessing three BB-resistant genes (Xa21, xa13 and xa5) and is highly popular in the southern parts of India. As the BB pathogen is highly dynamic and the evolution of pathogen virulence against the deployed resistance genes is common, we adde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 29 publications
1
48
0
Order By: Relevance
“…The analysis of variance showed highly significant value for all the traits undue study (Table 1). Kernel length of the introgression lines varied from 5.26 cm (ICF 2 -TH-625-588) to 6.46 cm (ICF 2 -TH-625-21), the kernel breadth varied (6), while the remaining lines had a slightly higher value (7). The KLAC of the lines were ranged from 8.43 to 9.97 mm but few lines were found to be better than Tellahamsa (9.43 mm).…”
Section: Agro-morphological and Quality Characters Of Selected Icf 2 mentioning
confidence: 96%
See 2 more Smart Citations
“…The analysis of variance showed highly significant value for all the traits undue study (Table 1). Kernel length of the introgression lines varied from 5.26 cm (ICF 2 -TH-625-588) to 6.46 cm (ICF 2 -TH-625-21), the kernel breadth varied (6), while the remaining lines had a slightly higher value (7). The KLAC of the lines were ranged from 8.43 to 9.97 mm but few lines were found to be better than Tellahamsa (9.43 mm).…”
Section: Agro-morphological and Quality Characters Of Selected Icf 2 mentioning
confidence: 96%
“…oryzae (Xoo) reduces rice yield drastically by declining photosynthetic area [6]. Disease survey data from the last 34 years within rice cultivating agroclimatic regions of India indicated that BB geographically spread rapidly, as a result of which, in recent years the extent of yield loss due to BB is more than 50% [7]. None of the several tested chemicals or antibiotics could control the BB infestation completely [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Breeding BB resistant rice varieties and hybrids is the best strategy for managing the BB disease in rice [ 10 ]. To date, at least 41 BB resistance genes have been identified,and some of them viz ., Xa4 , xa5 , xa13 , Xa21 have been extensively used for development of BB resistant rice varieties [ 11 , 12 , 13 , 14 , 15 ] ( Table 1 ). However, large scale and long-term cultivation of varieties and hybrids with a single gene results in the breakdown of resistance due to a high degree of pathogenic variation [ 12 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…O. glaberrima accessions were screened from 2016 to 2019 using a local virulent isolate of Xoo viz., IX-020 (Yugander et al, 2018). The test entries along with recurrent parent and resistant check were raised in mud pots following the required care and fertilizer applications to raise healthy plants.…”
Section: Screening Of O Glaberrima For Bacterial Blight Resistancementioning
confidence: 99%